Action learning and action research : genres and approaches - Zuber-Skerritt, Ortrun; Wood, Lesley (Emerald Publishing Limited, 2019)
Action Research (AR) is an ideal methodology to enable practical and emancipatory outcomes, as well as to generate relevant and authentic theory. Consequently, it has gained popularity worldwide. However, this emerging paradigm of AR in the Social Sciences has been widely misunderstood and misused by researchers, educators and practitioners. The integration of Action Learning with Action Research deepens understanding and contributes to new knowledge about the theory, practice and processes of Action Learning (AL) and Action Research (AR). It clarifies what constitutes AL/AR in its many forms and what it is not. AL and AR enable participants to effectively approach increasingly complex global challenges confronting humankind in this twenty-first century, collectively achieve practical, emancipatory and sustainable outcomes and generate relevant, authentic theory. This book, written by internationally renowned experts, is the first to provide a comprehensive overview of the main genres and approaches of AL/AR. They explain the genre of their expertise, reflect on their rich experiences with it, and consider both the common features shared across the AL/AR paradigm and what is distinctive about the particular genre they overview. This book discusses the what, why and how of their particular approach and will prove invaluable for researchers and practitioners alike.